Implementasi Pembelajaran Matematika Realistik untuk Peningkatan Hasil Belajar Siswa - Nurhafni Nurhafni (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
The purpose of this study was to determine the improvement of mathematics learning outcomes in fractional material by applying realistic mathematics learning in class IV.B SD Negeri 1 Langsa. The research method used is Classroom Action Research (CAR) with two cycles. The research subjects were conducted in class IV.B in 2014/2015. The location of the research was carried out at SD Negeri 1 Langsa. From the results of the study, it was found that there was an increase in learning outcomes in fractional material using realistic mathematics learning for grade IV.B students at SD Negeri 1 Langsa. Where the increase in the class average value of 60.92 in the pre-cycle rose to 76.05 in the first cycle and rose to 85.21 in the second cycle. At the end of the learning process the students were very active and there was a change in student understanding for the better so that student learning outcomes increased, thus it can be concluded that the application of realistic mathematics learning to fractions material can improve learning outcomes for grade IV.B students at SD Negeri 1 Langsa. So it is suggested that teachers can use realistic mathematics learning when teaching mathematics learning.